2013
DOI: 10.4103/2229-5070.122143
|View full text |Cite
|
Sign up to set email alerts
|

A study of prevalence of intestinal parasites and associated risk factors among the school children of Itahari, Eastern Region of Nepal

Abstract: Introduction:Intestinal parasitic infestation is a major public health problem in children of developing countries Because of poor socio-economic conditions and lack of good hygienic living. The aims of this study were to measure the prevalence of intestinal parasitic infestations and to identify risk factors associated with parasitic infestations among the school children of Itahari Municipality.Materials and Methods:The cross-sectional study was conducted in Grade VI, VII and VIII in Government and private s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
34
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 9 publications
(14 reference statements)
18
34
1
2
Order By: Relevance
“…This is in the line withSaka et al, (2014) (55) , andHaftu et al, (2014) (33) . On the other hand Al-Mohammed et al, (2010) (56) , and Sah et al, (2013) (57) found that hand washing after defecation was significantly associated with the prevalence of intestinal parasitic infection. The present study revealed that, about three quarter of infected students by parasites and slightly less than one quarter of non-infected students by parasites respectively, had moderate anemia and more than half of non-infected students by parasites and about (15.7%) of infected students had mild anemia ( figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…This is in the line withSaka et al, (2014) (55) , andHaftu et al, (2014) (33) . On the other hand Al-Mohammed et al, (2010) (56) , and Sah et al, (2013) (57) found that hand washing after defecation was significantly associated with the prevalence of intestinal parasitic infection. The present study revealed that, about three quarter of infected students by parasites and slightly less than one quarter of non-infected students by parasites respectively, had moderate anemia and more than half of non-infected students by parasites and about (15.7%) of infected students had mild anemia ( figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from different part of Ethiopia [2,5,[9][10][11][12] and outside Ethiopia [4,7] reported a prevalence of 22.7-79.8%. There was higher prevalence in this study compared to studies conducted in India and Nepal [4,7]. This might indicate better personal and environmental sanitation practice in the study area of those countries.…”
Section: Discussionmentioning
confidence: 99%
“…Globally two billion individuals were infected with intestinal parasites; of these majorities were children in resourcelimited areas [2,3]. World Health Organization estimated 800-1000 million cases of Ascariasis, 700-900 million of Hookworm infection, 500 millions of Trichuriasis, 200 million of Giardiasis and 500 million of Entamoeba histolytica worldwide [4]. In sub-Saharan African countries, up to 250 million people are infected with at least one intestinal nematodes [5].…”
Section: Introductionmentioning
confidence: 99%
“…[3] The WHO estimated that globally, there are 800-1000 million cases of ascariasis, 700-900 million of hookworm infection, 500 millions of trichuriasis, 200 million of giardiasis, and 500 million of amoebiasis. [4] Intestinal helminths infestations are the most common infestations among school-age children and they tend to occur in high intensity in this age group and lead to nutritional deficiency, including iron deficiency anemia, seizures, portal hypertension, chronic diarrhea, and impaired physical development in children which will have negative consequences on cognitive function and learning ability. [5,6] The lack of access to clean water, improved sanitation and adequate hygiene (WASH), low socioeconomic status, illiteracy, hot and humid tropical climate, and inadequate medical care largely attributes to the burden of these neglected tropical diseases.…”
Section: Introductionmentioning
confidence: 99%